Geo-Risk 2023 : Developments in Reliability, Risk, and Resilience. - Ching, Jianye (Geotechnical Special Publications, 2023)
GSP 346 contains 43 peer-reviewed papers on new developments in reliability, risk, and resilience in geotechnical engineering presented at Geo-Risk 2023, held in Arlington, Virginia, July 23-26, 2023.